Защита Гурова - Леонов Николай Иванович (Серия "Черная кошка", 1997)
Книга в суперобложке. Экземпляры: ф-23 (20230123) / Инвентарный номер: 58956 / Цена: 30.00 / Сис.шифр: Р2 / Авт.знак: Л 47 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-445.7